Numerical simulation of flood wave propagation in two-dimensions in densely populated urban areas due to dam break - Haltas, Ismail; Elçi, S.; Tayfur, G. (Springer, 2016)
Dams are important structures having many functions such as water supply, flood control, hydroelectric power and recreation. Although dam break failures are very rare events, dams can fail with little warning and the damage at the downstream of the dam due to the flood wave can be catastrophic. During a dam failure, immense volume of water is mobilized at very high speed in a very short time. The momentum of the flood wave can turn to a very destructive impact force in residential areas. Therefore, from risk point of view, understanding the consequences of a possible dam failure is critically important. This study deals with the methodology utilized for predicting the flood wave occurring after the dam break and analyses the propagation of the flood wave downstream of the dam. The methodology used in this study includes creation of bathymetric, DEM and land use maps; routing of the flood wave along the valley using a 1D model; and two dimensional numerical modeling of the propagation and spreading of flood wave for various dam breaching scenarios in two different urban areas. Such a methodology is a vital tool for decision-making process since it takes into account the spatial heterogeneity of the basin parameters to predict flood wave propagation downstream of the dam. Proposed methodology is applied to two dams; Porsuk Dam located in Eskişehir and Alibey Dam located in Istanbul, Turkey. Both dams are selected based on the fact that they have dense residential areas downstream and such a failure would be disastrous in both cases. Model simulations based on three different dam breaching scenarios showed that maximum flow depth can reach to 5 m at the border of the residential areas both in Eskişehir and in Istanbul with a maximum flow velocity of 5 m/s and flood waves having 0.3 m height reach to the boundary of the residential area within 1 to 2 h. Flooded area in Eskişehir was estimated as 127 km2, whereas in Istanbul this area was 8.4 km2 in total.
Keywords: Bathymetry; DEM; Land use maps; Dam break; Flood wave; Numerical modeling; Urban area; Flood maps